Uterine scars after caesarean delivery: From histology to the molecular and ultrastructural level. - Paping, Alexander; Basler, Clara; Ehrlich, Loreen; Fasting, Carlo; Melchior, Kerstin; Ziska, Thomas; Thiele, Mario; Duda, Georg N.; Timm, Sara; Ochs, Matthias; Rancourt, Rebecca C.; Henrich, Wolfgang; et al. (Wound Repair & Regeneration)
Uterine rupture during a trial of labor after caesarean delivery (CD) is a serious complication for mother and fetus. The lack of knowledge on histological features and molecular pathways of uterine wound healing has hindered research in this area from evolving over time. We analysed collagen content and turnover in uterine scars on a histological, molecular and ultrastructural level. Therefore, tissue samples from the lower uterine segment were obtained during CD from 16 pregnant women with at least one previous CD, from 16 pregnant women without previous CD, and from 16 non‐pregnant premenopausal women after hysterectomy for a benign disease. Histomorphometrical collagen quantification showed, that the collagen content of the scar area in uterine wall specimens after previous CD was significantly higher than in the unscarred myometrium of the same women and the control groups. Quantitative real‐time PCR of uterine scar tissue from FFPE samples delineated by laser microdissection yielded a significantly higher COL3A1 expression and a significantly lower COL1A2/COL3A1 ratio in scarred uteri than in samples from unscarred uteri. Histological collagen content and the expression of COL1A2 and COL3A1 were positively correlated, while COL1A2/COL3A1 ratio was negatively correlated with the histological collagen content. Transmission electron microscopy revealed a destroyed myometrial ultrastructure in uterine scars with increased collagen density. We conclude that the high collagen content in uterine scars results from an ongoing overexpression of collagen I and III. This is a proof of concept to enable further analyses of specific factors that mediate uterine wound healing.